Investigating key success factors in adopting knowledge management system - Noordin, Mohamad Fauzan; Othman, Roslina; Zakaria, Noor Azura (IDOSI Publication, 2013)
The important of KMS could not be denied in this competitive era especially when the organization has to focus on their sustainability and to remain competitive advantage. The KMS can be considered as a pond of knowledge in the respective organization whereby the accessible of the knowledge is in the right place, right time and by the right person. The adoption of KMS could assist the organization to maintain and improve their productivity. In order to successfully adopting and implementing KMS, the identification of the key success factors in the respective environment and population is important to ensure that the core factors have been tackled. Most of the studies have elaborated thoroughly on the successful factors in implementing knowledge management as a whole but only few has discussed mainly on KMS implementation. This study provides empirical evidence in the key success factors of adopting and implementing KMS in the Malaysian context. There were 83 valid responses went for data analysis to perform the reliability and factor loading. Results derived from the analysis show that the limitations to current KMS, inhibitors in terms of infrastructure and reluctance attitude and strategies have positively correlated with the successful of KMS implementation. These findings can be one of the insights to the organizations to embark on the strategies and guidelines prior to adopting the KMS.